Interspecies Communication and Periodontal Disease - Ajay Mahajan; Baljeet Singh; Divya Kashyap; Amit Kumar; Poonam Mahajan (The Scientific World Journal)
More than 500 bacterial strains may be found in dental plaque. In the beginning, the emphasis was laid on the isolation of bacteria in pure culture to define their properties. However, now, it has been well established that in nature the bacteria exist as a member of polymicrobial community or consortium of interacting species. Interactions among human oral bacteria are integral to the development and maturation of the plaque. These interactions occur at several levels including physical contact, metabolic exchange, small-signal molecule-mediated communication, and exchange of genetic material. This high level of interspecies interaction benefits the microorganism by providing a broader habitat range, effective metabolism, increasing the resistance to host defence, and enhancing their virulence. This generally has a detrimental effect on the host and is attributed to many chronic infections which poses a therapeutic challenge.